2018
DOI: 10.1111/ina.12462
|View full text |Cite
|
Sign up to set email alerts
|

Detailed investigation of ventilation rates and airflow patterns in a northern California residence

Abstract: Building ventilation rates and indoor airflow conditions influence occupants' exposure to indoor air pollutants. By making time- and space-resolved measurement of 3 inert tracers steadily released in a single-family house in California for 8 weeks in summer and 5 weeks in winter, this study quantifies the air change rate of the living zone with 2-hour time resolution; estimates airflow rates between the living zone, attic, and crawlspace; and characterizes mixing of air in the split-level living space. Occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 32 publications
(93 reference statements)
0
81
0
Order By: Relevance
“…Key approximations made in this calculation are (a) that the occupied internal volume of the house can be effectively considered as well‐mixed and (b) that only indoor emissions and air change between indoor and outdoor air influence indoor‐air concentrations. These approximations are supported by three important observations: (a) tracer results showed that air in the upper and lower living spaces mixed fairly well; (b) the crawlspace and attic generally served as one‐way paths for airflow into and out of living zone, respectively; and (c) VOC composition in the crawlspace was similar to that outdoors. Under this approximation, the mass balance of a VOC in the living zone is given by the following equation:dCindtV=Eρ-A·false(Cin-Coutfalse)·V,where C in = C in ( t ) and C out = C out ( t ) are the concentrations in the living zone and outdoors (ppb; part per billion by volume); V is the volume of the living zone (m 3 ); E = E ( t ) is the emission rate in the living zone (mg h −1 ); ρ is the gas density for the compound (mg mm −3 ); and A = A ( t ) is the living‐space air‐change rate (h −1 ).…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…Key approximations made in this calculation are (a) that the occupied internal volume of the house can be effectively considered as well‐mixed and (b) that only indoor emissions and air change between indoor and outdoor air influence indoor‐air concentrations. These approximations are supported by three important observations: (a) tracer results showed that air in the upper and lower living spaces mixed fairly well; (b) the crawlspace and attic generally served as one‐way paths for airflow into and out of living zone, respectively; and (c) VOC composition in the crawlspace was similar to that outdoors. Under this approximation, the mass balance of a VOC in the living zone is given by the following equation:dCindtV=Eρ-A·false(Cin-Coutfalse)·V,where C in = C in ( t ) and C out = C out ( t ) are the concentrations in the living zone and outdoors (ppb; part per billion by volume); V is the volume of the living zone (m 3 ); E = E ( t ) is the emission rate in the living zone (mg h −1 ); ρ is the gas density for the compound (mg mm −3 ); and A = A ( t ) is the living‐space air‐change rate (h −1 ).…”
Section: Methodsmentioning
confidence: 64%
“…The time‐dependent indoor concentration, C in , is approximated as the weighted mean of VOC concentrations measured in the kitchen and bedroom area. The procedures to calculate values of Cinfalse(t+normalΔtfalse)-Cinfalse(tfalse), C¯in, and C¯out are described in the supplement and are consistent with the procedures to determine the air‐change rate using measured tracer concentrations …”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…House airflows and air exchange rates were acquired through high–time resolution measurements of an inert tracer (butene‐d3, CD 3 CH 2 CH=CH 2 , 98%; Cambridge Isotope Laboratories, Inc,) continuously released inside the residence. The tracer was detected using proton transfer reaction time‐of‐flight mass spectrometry (PTR‐TOF‐MS) following previously reported methods . Using the determined flow rates (m 3 h −1 ), the effective emission rate ( E , mg h −1 ) of gas‐phase SVOCs from indoor sources to the indoor air was estimated using the following equation:E=dCIndoordtV+FlowRatefalse(CIndoor-COutdoorfalse)Here, C Indoor and C Outdoor refer to the SV‐TAG measured indoor and outdoor gas‐phase SVOC concentrations, respectively (in mg m −3 ), obtained by subtracting the particle‐only SVOC concentration (denuded sample) from the total gas‐plus‐particle SVOC concentration (undenuded sample).…”
Section: Experimental Methodsmentioning
confidence: 99%